2015
DOI: 10.1177/1535370214567612
|View full text |Cite
|
Sign up to set email alerts
|

Effective suppression of nitric oxide production by HX106N through transcriptional control of heme oxygenase-1

Abstract: Heme oxygenase-1 (HO-1) has been suggested to be a key neuroprotective enzyme because of its widespread distribution in the brain as well as its strong antioxidative effects. HX106N, a water-soluble botanical formulation, has previously been demonstrated to prevent amyloid b-induced memory impairment and oxidative stress in mice by upregulating HO-1 levels. In this study, the underlying molecular mechanisms of HX106N-induced HO-1 expression were investigated using BV-2 cells, a murine microglial cell line, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Although it has been reported that HO-1 induces NO during cellular senescence, the induction of HO-1 inhibits iNOS to reduce NO by oxidative injury (22). CO and biliverdin, the products of HO-1, are also known to inhibit iNOS (23)(24)(25). Therefore, controlling HO-1 expression is pivotal in modulating anti-inflammatory responses.…”
Section: Anti-inflammatory Effects Of Methanol Extract From Peperomia...mentioning
confidence: 99%
“…Although it has been reported that HO-1 induces NO during cellular senescence, the induction of HO-1 inhibits iNOS to reduce NO by oxidative injury (22). CO and biliverdin, the products of HO-1, are also known to inhibit iNOS (23)(24)(25). Therefore, controlling HO-1 expression is pivotal in modulating anti-inflammatory responses.…”
Section: Anti-inflammatory Effects Of Methanol Extract From Peperomia...mentioning
confidence: 99%
“…HX106 is a nutraceutical composed of four different herbal extracts: Arilli of Dimocarpus longan Loureiro (Sapindaceae), tubers of Liriope platyphylla Wang and Tang (Liliaceae), roots of Salvia miltiorrhiza Bunge (Lamiaceae) and rhizomes of Gastrodia elata Blume (Orchidaceae). These compositions were selected and mixed according to the traditional knowledge and information from previous studies [ 24 , 25 ]. HX106 has been reported to improve memory function possibly mediated by the suppression of oxidative stress, neuroinflammation and accumulation of amyloid beta and tau tangle [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compositions were selected and mixed according to the traditional knowledge and information from previous studies [ 24 , 25 ]. HX106 has been reported to improve memory function possibly mediated by the suppression of oxidative stress, neuroinflammation and accumulation of amyloid beta and tau tangle [ 24 , 25 , 26 ]. Based on these results, HX106 has been applied into clinical study (NCT01956097).…”
Section: Introductionmentioning
confidence: 99%